Learning Laboratory: An Integrative Learning Design for International Business in a Complex Dynamic World. (June 2022) - Zettinig, Peter; Aleem, Majid; Majdenic, Danijela; Berry, Michael
Graduates of international business (IB) programs are facing a complex dynamic world in which they need both specific and generalist knowledge they can activate in socially negotiated situations. Their competencies must go beyond narrowly applying knowledge, which requires open minds, transferable social competencies, and skills for crossing multiple boundaries to serve their organizations to deal with global challenges. In order to facilitate the development of such professional and personal competencies, we established a learning laboratory, a space providing simulated opportunities in real multinational organizational structures, where students experiment with intercultural encounters while solving business challenges and reflect on their experiences to develop their managerial practices. This article introduces our instructional innovation by discussing the underlying learning framework and providing an illustration of the approach. The lab has three main learning outcomes: building conceptual knowledge, developing sociocultural practices in multinational organizations, and enhancing self-awareness and reflective competencies. At the core of the lab are a series of IB strategy challenges which students solve by organizing, managing, and leading global virtual teams (GVTs) that are formed with members from five overseas universities. We detail the alignment of our framework, review the actions and interactions that facilitate learning, and discuss learning effectiveness and implementation of the lab.